2010
DOI: 10.1002/syn.20746
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and postnatal exposure to bisphenol a induces anxiolytic behaviors and cognitive deficits in mice

Abstract: Bisphenol A (BPA), an environmental endocrine-disrupting chemical, has been extensively evaluated for reproductive toxicity and carcinogenicity. However, little is known about the behavioral and neurochemical effects of BPA exposure. This study examined whether chronic daily exposure to an environmental endocrine-disrupting chemical, bisphenol A [(BPA); 100 microg/kg/day or 500 microg/kg/day, p.o.], from prenatal Day 7 to postnatal Day 36 would lead to changes in anxiety and memory in mice. First, we observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(107 citation statements)
references
References 49 publications
5
99
0
1
Order By: Relevance
“…14,38 Gestational BPA exposures might affect endocrine or other neurotransmitter pathways and disrupt sexual differentiation of the brain, to alter behavior in a genderdependent manner. 39,40 However, the exposures and behavioral end points used in some animal studies might not be relevant or comparable to human cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,38 Gestational BPA exposures might affect endocrine or other neurotransmitter pathways and disrupt sexual differentiation of the brain, to alter behavior in a genderdependent manner. 39,40 However, the exposures and behavioral end points used in some animal studies might not be relevant or comparable to human cases.…”
Section: Discussionmentioning
confidence: 99%
“…11 Experimental studies with animals indicated that gestational BPA exposure disrupts normal neurodevelopment, affecting sexually dimorphic behaviors such as aggression, anxiety, exploration, and spatial memory. [12][13][14] Sexually dimorphic clinical disorders such as attention-deficit/hyperactivity disorder, autism, and depression might be clinical correlates of these animal behaviors and might be related to early-life disruption of the endocrine system. 15,16 These observations suggest that sexually dimorphic behavioral traits may serve as sensitive end points in epidemiological studies.…”
mentioning
confidence: 99%
“…Later, in 2010, two papers reported a decrease of NMDA receptors in mice hippocampus. Prenatal and postnatal exposure to BPA at low doses (100-500 µg/Kg/day) decreased NMDA (not subtype specified) and dopamine receptors, and induced anxiolytic behaviors as well as cognitive deficits [45]. At high doses (50-50000 µg/Kg/day) BPA inhibited the expression of NMDA receptors GluN1, GluN2A and GluN2B and ERβ, impairing learning and memory [46] That same year, two other papers reported opposite effects of low doses of BPA on NMDA receptors in rat hippocampus: a decrease in the expression of NMDA receptors [47] and an increase in NMDA receptors GluN2B mediated by ERβ phosphorylation promoting dynamic changes in hippocampal dendritic morphology [48] A further paper by Xu and coworkers reported again an increase in the expression of NMDA receptors GluN1and…”
Section: Ionotropic Glutamate Receptorsmentioning
confidence: 99%
“…Experimental studies with animals indicated that gestational BPA exposure disrupts normal neurodevelopment, affecting aggression, anxiety, exploration, and spatial memory. 23,24 BPA exposure also induces prefrontal and hippocampal spin synapse loss in rodents which may result in cognitive dysfunction. 25 The animal literature suggests that exposure to BPA affects the development of the forebrain dopaminergic system via binding to estrogen dependent dopaminergic receptors that are important for regulation of behavioral impulses.…”
Section: Discussionmentioning
confidence: 99%